Application of the Multiple Linear Regression Method in Forecasting the Amount of Drug Supply at the Health Center - Riki Ternando; Jusuf Wahyudi; Dewi Suranti (Penerbit Jurnal Indonesia, 2022)
Sukamerindu Health Center is one of the health centers in the city of Bengkulu. Drug management at the puskesmas has utilized an office application package, namely excel, but this utilization has not been fully implemented, because there is still a manual process where drug data collection is filled in through the books that have been provided, then only recapitulated at the end of the month. This sometimes makes it difficult for the puskesmas to manage the availability of drugs at the puskesmas. The application for forecasting the amount of drug supply at the UPTD Sukamerindu Health Center in Bengkulu City was made using the Visual Basic .Net programming language by applying the Multiple Linear Regression Method for the forecasting process. In determining the results of the forecast for the following month and year, there are 3 supporting variables used, namely demand, use, and supply of drugs in the previous month and year. Based on data on the 500 mg Amoxicillin Capsule, where there were 36 data analyzed from January 2019 to December 2021, the prediction results for the number of drug supplies in January 2022 using the Multiple Linear Regression Method were 13066, with a prediction error rate of 7.10%. . Based on testing the application for forecasting the amount of drug inventory at the UPTD Puskesmas Sukamerindu, Bengkulu City, it was found that the functionality of the application ran according to expectations .